Advances in Applied Biotechnology - Zhang, Tong-Cun (Springer, 2015)
At the ICAB 2014, researchers from around the world will gather to discuss the latest scientific research, findings and technologies concerning Microbial Genetics and Breeding, Optimization and Control of Biological Processes, Biological Separation and Biological Purification, and Advances in Biotechnology. This conference will provide a platform for academic exchange on the application of biotechnology between domestic and international universities, research institutes, corporate experts and scholars. The participants will focus on the international development and future trends. The event will lay a solid foundation for addressing key technical challenges in various areas of applied biotechnology, providing opportunities to promote the development and expansion of the biotechnology industry.